Musical Learning For Early Childhood Through Listening Approach, Singing, Playing - Nusantoro, Jati Ulung; Supratno, Haris; Lodra, I Nyoman (International Journal for Educational and Vocational Studies, 2019)
Course institutions is one of non-formal education as a substitute, complementary, enhancement, and education outside of school. One of the best non-formal institutions to develop early childhood talent is the Yamaha Music School course institute. This is what makes researchers interested in learning which is done by Yamaha Music School course for early childhood. This type of research uses qualitative research, ranging from lesson planning, implementation of learning to evaluation of learning. Data collection techniques used non-contributory types of observation, documentation and structured interviews conducted face-to-face. The subjects of this study were early childhood at the age of 3 years and a lecturer in Wonderland Music Class Moshi-Moshi Yamaha Music School. The form of lesson planning for wonderland music classes ranging from materials, methods, models, media and time allocation has been designed by the Yamaha Music School Foundation of Japan but can be developed by each teacher according to the situations that occur in the classroom during the learning process. The classroom learning atmosphere created by the teacher is great for the child to feel good about music. The results of the evaluation conducted at the Wonderland studio class only provide a learning award in the classroom with that of fiesta music and concert classes.